Islamic Republic of Afghanistan : Seventh Review Under the Staff-Monitored Program and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; Staff Supplement; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for the Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report ;, 2006)
Afghanistan's economy continued to perform strongly under the staff-monitored program, resulting in rapid economic growth, inflation declining to single-digit levels, and the international reserves position strengthening further. At the same time, the authorities implemented key structural reforms in the fiscal and monetary areas, while bringing to fruition the political framework envisaged under the 2001 Bonn agreement. Risks remain considerable. In addition to those related to the security situation, the government faces the challenges of dealing with persistent opium-related activities, weak implementation capacity, and uncertainties about donor assistance.